Targeting PPARγ via SIAH1/2-mediated ubiquitin-proteasomal degradation as a new therapeutic approach in luminal-type bladder cancer - Chih-Chieh Tu; Tsung-Han Hsieh; Cheng-Ying Chu; Yu-Chen Lin; Bo-Jyun Lin; Chun-Han Chen (Cell Death and Disease)
Abstract Bladder cancer (BC) is the second most prevalent genitourinary malignancy worldwide. Despite recent approvals of immune checkpoint inhibitors and targeted therapy for muscle invasive or recurrent BC, options remain limited for patients with non-muscle invasive BC (NMIBC) refractory to Bacillus Calmette-Guérin (BCG) and chemotherapy. NMIBC is more frequently classified as a luminal subtype, in which increased PPARγ activity is a key feature in promoting tumor growth and evasion of immunosurveillance. Cinobufotalin is one of the major compound of bufadienolides, the primary active components of toad venom that has been utilized in the clinical treatment of cancer. We herein focused on cinobufotalin, examining its anticancer activity and molecular mechanisms in luminal-type NMIBC. Our results newly reveal that cinobufotalin strongly suppresses the viability and proliferation of luminal BC cells with minimal cytotoxic effects on normal uroepithelial cells, and exhibits significant antitumor activity in a RT112 xenograft BC model. Mechanistically, our sub-G1-phase cell accumulation, Annexin V staining, caspase-3/8/9 activation, and PARP activation analyses show that cinobufotalin induces apoptosis in luminal-type BC cells. Cinobufotalin significantly inhibited the levels of PPARγ and its downstream targets, as well as lipid droplet formation and free fatty acid levels in RT112 cells. PPARγ overexpression rescued RT112 cells from cinobufotalin-induced apoptosis and mitigated the downregulation of FASN and PLIN4. Finally, we show seemingly for the first time that cinobufotalin promotes SIAH1/2-mediated proteasomal degradation of PPARγ in luminal BC cells. Together, these findings compellingly support the idea that cinobufotalin could be developed as a promising therapeutic agent for treating luminal-type NMIBC.